2012
DOI: 10.1038/ncomms1781
|View full text |Cite
|
Sign up to set email alerts
|

Soluble amyloid precursor protein-α modulates β-secretase activity and amyloid-β generation

Abstract: In sporadic age-related forms of Alzheimer’s disease (AD), it is unclear why amyloid-β (Aβ) peptides accumulate. Here, we show that soluble amyloid precursor protein-α (sAPP-α) decreases Aβ generation by directly associating with BACE1; thereby modulating APP processing. Whereas specifically targeting sAPP-α using antibodies enhances Aβ production, in transgenic mice with AD-like pathology, sAPP-α overexpression decreases β-amyloid plaques and soluble Aβ. In support, immunoneutralization of sAPP-α increases AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(137 citation statements)
references
References 58 publications
2
131
0
Order By: Relevance
“…In addition, it has been shown that over-expression of human sAPPα ameliorates Aβ pathogenesis in APP/ PS1 mice. Correspondingly, immunoneutralization of sAPPα by antibody causes hippocampal neuronal apoptosis in this model (Obregon et al 2012). These evidences, taken together, highly suggest that elevated α-secretase levels in neuronal cell bodies, give them the ability to produces neuroprotective sAPPα and maximally reduce neurotoxic Aβ production, in turn protects hippocampal neurons in the relatively long-term survival in AD-like pathology.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, it has been shown that over-expression of human sAPPα ameliorates Aβ pathogenesis in APP/ PS1 mice. Correspondingly, immunoneutralization of sAPPα by antibody causes hippocampal neuronal apoptosis in this model (Obregon et al 2012). These evidences, taken together, highly suggest that elevated α-secretase levels in neuronal cell bodies, give them the ability to produces neuroprotective sAPPα and maximally reduce neurotoxic Aβ production, in turn protects hippocampal neurons in the relatively long-term survival in AD-like pathology.…”
Section: Discussionmentioning
confidence: 57%
“…In the broader context of all these interactions and balance, TrkB FL beneficial effects can be associated even with over-all increased APP levels. Very recently it has been shown that sAPP-, the fragment generated by ADAMs from APP, can inhibit BACE1 activity [30] therefore TrkB FL could be involved in this mechanism by promoting sAPP- production and increasing BACE1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, in the trophic, anti-amyloidogenic anti-AD pathway, APP is cleaved by an α-secretase (putatively ADAM10) to generate the two fragments sAPPα and αCTF. These latter fragments [30] support synaptic maintenance and can inhibit the β pathway as cleavage at the α site precludes β cleavage and because sAPPα itself is a BACE inhibitor [31,32].…”
Section: App Processingmentioning
confidence: 99%
“…As the α-site is within the Aβ cognate region, α-cleavage precludes Aβ formation. In addition, sAPPα itself can act as a BACE inhibitor [31,32] while αCTF is an inhibitor of γ-secretase [33]. Alternatively, in the anti-trophic pro-AD pathway, FL-APP can interact with BACE resulting in dimerization, endocytosis, and cleavage in the acidic endosomal compartment, generating sAPPβ and βCTF.…”
Section: Mutations In Adam10 and At Appα-and β-Cleavage Sites Alter Amentioning
confidence: 99%
See 1 more Smart Citation